KAJIAN HUKUM TENTANG DELIK PENGGELAPAN Studi Kasus Putusan Pengadilan Negeri Surakarta (Nomor: 05 / Pid.B / 2015 / PN. Skt dan Nomor: 169/Pid.B/2014/PN Skt) - WISENO, DJOKO (Dinamika Hukum, 2015)
The purpose of this research is to review and to analyze the implementation of the legal consideration of judges in convicting toward the offense perpetrator of embezzlement on district court decision and comparison of judge’s decision in the crime of embezzlement on Surakarta district court.Research focus background is based on the aspect of material penal law implementation existence by legal prosecutor toward crime of embezzlement and what the legal considerations are in deciding crime of embezzlement cases. Whereas the case which being analyzed is the legal review about acts of embezzlement offense (Case Study of District Court of Surakarta’s decision no: 169/Pid.B/2014/PN Skt and as the comparison decision no 05/Pid.B/PN.Skt). Keyword : acts of embezzlement offense and judge’s decision